Teologi Katolik Roma - Harjaya Situmeang; Yersi Hotmauli Berutu; Suang Manik; Adi Suhenra Sigiro (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This article examines the teachings, doctrines, and practices within Roman Catholic Theology with the aim of providing a comprehensive understanding of the liturgical structure, teachings, and leadership of the Catholic Church. The research was conducted using a qualitative method through literature analysis from various journals, books, and related scholarly sources. The findings indicate that Roman Catholic Theology is rooted in Sacred Scripture, Sacred Tradition, and the Magisterium, and it presents fundamental differences from other Christian theologies, particularly in its concepts of salvation, doctrinal authority, and worship practices. In addition, this study highlights historical developments, the influence of ecumenical councils, and the roles of Mary and the sacraments in the life of Catholic faith. These findings are expected to help readers understand the characteristics and dynamics of Roman Catholic Theology in its historical context and contemporary challenges.